If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8m + -7 = 2 + 9m + -10m Reorder the terms: -7 + -8m = 2 + 9m + -10m Combine like terms: 9m + -10m = -1m -7 + -8m = 2 + -1m Solving -7 + -8m = 2 + -1m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add 'm' to each side of the equation. -7 + -8m + m = 2 + -1m + m Combine like terms: -8m + m = -7m -7 + -7m = 2 + -1m + m Combine like terms: -1m + m = 0 -7 + -7m = 2 + 0 -7 + -7m = 2 Add '7' to each side of the equation. -7 + 7 + -7m = 2 + 7 Combine like terms: -7 + 7 = 0 0 + -7m = 2 + 7 -7m = 2 + 7 Combine like terms: 2 + 7 = 9 -7m = 9 Divide each side by '-7'. m = -1.285714286 Simplifying m = -1.285714286
| 3(d-8)+4= | | -14=5-g | | 6a/3b | | 9(7x-7)+4=11x-6 | | 4x-10=x+23 | | -a+8y= | | 3+z/4=-5 | | 2(y+5)=-10 | | c=by+ax | | x=4+53 | | 2.50r+5.30=55.20 | | 1x-4+5x-5=10+16x-10 | | X/3=29/6 | | 6x-3(-6x+15)=-165 | | x-4+5x-5=10+16x-10 | | 4a+8+28=8a | | 5x-6x+x-4+3x= | | 3f-1=19-2f | | 9y-1=6y+5 | | -8-3t+2=5t-6t | | 11=3x+2(-4x-12) | | -3=-3(2r-4) | | m-9m+4m-4= | | -18(-9/7)=14 | | 16.15+0.09h=16.90-0.11h | | a/3+17=10 | | 5b-4-9b-9= | | solvex^3-3x^2=9x-27 | | -3x-6=n | | -18(-7/9)=14 | | 3a+(2a-5)=13-2a-4 | | s^2+5s+8s+40= |